Contracting-out welfare services : comparing national policy designs for unemployment assistance - O'Sullivan, Siobhan, 1974-; Considine, Mark, 1953-; Ohio Library and Information Network (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2015)
"Contracting-out Welfare Services: Comparing National Policy Designs for Unemployment Assistance is an edited collection focused on the design and re-design of welfare-to-work systems around the world"--
7 Broken Hierarchies, Quasi-markets and Supported Networks -- A Governance Experiment in the Second Tier of Germany's Public Employment ServiceIntroduction; Broken Hierarchies: The Structure and Governance of the German Public Employment Service before and after the Hartz Reforms; The Federal Programme Perspective 50plus in the Context of Labour Market and Pension Reforms; Perspective 50plus as a Relatively Successful Programme: Some Stylized Results from the Evaluation; Explaining the Success of the Programme through the Features of its Governance; Discussion; Conclusion; References
"Originally published as Volume 48, Issue 2 of Social Policy & Administration."
Includes bibliographical references and index
Keywords: Social service -- Contracting out -- Europe; Public welfare -- Europe; Unemployment -- Europe; Public-private sector cooperation -- Europe; Public administration -- Europe; Electronic books